(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У даній статті автор розглядає зміст та сутність творчої комунікативної позиції майбутніх учителів, аналізує різні підходи до тлумачення цього поняття в наукових джерелах. Ключові слова: творча комунікативна позиція, позиція особистості, творча особистість. In this article the author examines the content and essence of the creative communication of the future teachers positions, analyzes the different approaches to the interpretation of this concept in the scientific literature. Key words: creative communicative position, the position of the individual, creative person.